Post - surgical acute abdomen - Borja Ochoa, José Luis; Moncayo, Fernando; Mendoza C, Walter (Revista Universidad de Guayaquil, 2011)
The postoperative acute abdomen is a plurisintomatica whose main causes lie in complications that can occur in a surgery performed. In the postoperative patient, peritonitis secondary to a complication occupies 20 to 45% of international statistics, within these, 70% may develop sepsis, which when it is not controlled it can cause a syndrome of multiple organic dysfunction with a high mortality; national and local complications vary between 10 to 20 per cent of statistics carried out in hospital units. Evaluate the postoperative acute abdomen is not an easy task since the postoperative pain, the normal adynamic ileus of a patient underwent surgery may mask the table clinical and more even if the patient is with ventilation and unstable hemodinamicamente. This clínico-quirúrgica entity currently occurs frequently, that is why it is necessary to the health professional is pending on the evolution of the patient to identify and diagnose these complications early that will be caused a postoperative acute abdomen, an essential condition to ensure even the same life of the patient.